Timing of Verification Procedures: Monitoring versus Auditing - Roland Strausz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2005)
This paper studies the strategic effect of a difference in timing of verification in an agency model. A principal may choose between two equally efficient verification procedures: monitoring and auditing. Under auditing the principal receives additional information. Due to a double moral hazard problem, there exists a tension between incentives for effort and incentives for verification. Auditing exacerbates this tension and, consequently, requires steeper incentive schemes than monitoring. Hence, auditing is suboptimal if 1) steep incentives structures are costly to implement due to bounded transfers, or 2) steep incentive schemes induce higher rents due to limited liability. verification in an agency model. A principal may choose between two equally efficient verification procedures: monitoring and auditing. Under auditing the principal receives additional information. Due to a double moral hazard problem, there exists a tension between incentives for effort and incentives for verification. Auditing exacerbates this tension and, consequently, requires steeper incentive schemes than monitoring. Hence, auditing is suboptimal if 1) steep incentives structures are costly to implement due to bounded transfers, or 2) steep incentive schemes induce higher rents due to limited liability.
urn:nbn:de:bvb:19-epub-13515-0
Keywords: D82; 330; timing of verification; double moral hazard; monitoring; auditi